If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 10 + -6x = 6x + 40 Reorder the terms: 10 + 9x + -6x = 6x + 40 Combine like terms: 9x + -6x = 3x 10 + 3x = 6x + 40 Reorder the terms: 10 + 3x = 40 + 6x Solving 10 + 3x = 40 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 3x + -6x = 40 + 6x + -6x Combine like terms: 3x + -6x = -3x 10 + -3x = 40 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + -3x = 40 + 0 10 + -3x = 40 Add '-10' to each side of the equation. 10 + -10 + -3x = 40 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = 40 + -10 -3x = 40 + -10 Combine like terms: 40 + -10 = 30 -3x = 30 Divide each side by '-3'. x = -10 Simplifying x = -10
| -2(x-8)=4(x+1) | | 10x+7+5x=7x+31 | | (t+9)+(4t-15)= | | 17x+4=10-45 | | 12y+8=5y-5 | | 5(-4)-4y=20 | | (Gx)=6x^2-224x+4941 | | solvex^3-2x-1.5=0 | | x^3-2x-1.5=0 | | 172-6x=5x+18# | | r^2-10r+6=0 | | 3x+13=9x-11 | | 5y^3-8y^2+3y=0 | | 8x^2=7x+3 | | 50+2y=5y | | (x+2)(x-3)(3x+4)=0 | | -5y+7x=105 | | -67-8x=86-38x | | x^2+8kx+x=0 | | 18*1.6= | | -9-3x=3x+10 | | 3d+5=10 | | .4x+.3=3.5 | | 3+2x+3x-4x=15 | | 10x+6-9x=10 | | 20x-9=12x-98 | | 14+2x+4-x=32 | | 7+x=2*x | | 7+y=2*y | | 7+y=2xy | | x+3(x-3)=0 | | 36x^5-36x^4+6x^3-6x^2=0 |